HSD17B7 gene in self‐renewal and oncogenicity of keratinocytes from Black versus White populations - Xiaoying Xu; Beatrice Tassone; Paola Ostano; Atul Katarkar; Tatiana Proust; Jean‐Marc Joseph; Chiara Riganti; Giovanna Chiorino; Zoltan Kutalik; Karine Lefort; Gian Paolo Dotto (EMBO Molecular Medicine)
Abstract Human populations of Black African ancestry have a relatively high risk of aggressive cancer types, including keratinocyte‐derived squamous cell carcinomas (SCCs). We show that primary keratinocytes (HKCs) from Black African (Black) versus White Caucasian (White) individuals have on average higher oncogenic and self‐renewal potential, which are inversely related to mitochondrial electron transfer chain activity and ATP and ROS production. HSD17B7 is the top‐ranked differentially expressed gene in HKCs and Head/Neck SCCs from individuals of Black African versus Caucasian ancestries, with several ancestry‐specific eQTLs linked to its expression. Mirroring the differences between Black and White HKCs, modulation of the gene, coding for an enzyme involved in sex steroid and cholesterol biosynthesis, determines HKC and SCC cell proliferation and oncogenicity as well as mitochondrial OXPHOS activity. Overall, the findings point to a targetable determinant of cancer susceptibility among different human populations, amenable to prevention and management of the disease.